Persepsi Pemustaka terhadap Layanan Sirkulasi Perpustakaan di Dinas Perpustakaan dan Kearsipan Kabupaten Padang Pariaman - Zamzami, Mutiara; Nurizzati, Nurizzati (TSAQOFAH, 2025)
This study aims to describe user perceptions of circulation services at the Library and Archives Service of Padang Pariaman Regency. The type of research used is descriptive quantitative with a survey approach. Data were collected through questionnaires distributed to 89 respondents who were active library users. The research instrument covered four main aspects: service procedures, service speed, staff friendliness, and facility comfort. The results show that overall, users’ perceptions of circulation services fall into the very good category with a percentage of 86.75%. The highest rated aspect was staff friendliness, indicating that interpersonal interactions between staff and users are highly appreciated. Meanwhile, the aspect of facility comfort received the lowest score among the four aspects, though it still fell within the good category. These findings indicate that the circulation service has met user expectations and is generally functioning effectively. The conclusion of this study is that the quality of circulation services at the library is at a satisfactory level, although there is still room for improvement, particularly in the area of facilities. The practical implication of this research is the need for continuous evaluation and overall service quality enhancement to support user satisfaction and loyalty.